Ancient Egypt - Harris, Geraldine (New York : Facts on File, 1990)
Maps, charts, illustrations, and text explore the history and culture of ancient Egypt.
"An Equinox book"--T.p. verso.
Includes bibliographical references (p. 93) and index.
Keywords: Egypt -- Juvenile literature. -- To 640 A.D. -- Juvenile literature; Egypt -- Juvenile literature. -- Juvenile literature; Egypt -- History -- To 640 A.D.; Egypt -- Antiquities